STRATEGIES OF STREET VENDORS IN THE NEW ROAD AREA OF LOSARI KIDUL VILLAGE TO INCREASE INCOME - Atsaqolain, Nazil Alhamdi; Navilah, Ila; Haryati, Yati (Cirebon International Journal of Economics and Business, 2025)
Street vendors play a crucial role in the economy and have positive impacts, such as creating jobs, helping reduce unemployment, and increasing people's incomes to meet their living needs. The purpose of this study was to determine strategies for increasing the income of street vendors in Losari Kidul village. The author used a qualitative research method. With a case study approach, the data analysis technique in this study uses data reduction, data presentation, and conclusion drawing methods. The results of this study are the strategies used by street vendors in the Jalan Baru area of Losari Kidul Village to increase income in several ways , namely 1) maintaining product quality and product variants where traders always pay attention to the quality of the products they have and provide product variant offers to attract consumer interest. 2) setting prices based on raw materials and market prices in general. 3) conducting promotions where each trader has their own method of promotion, some use social media, and some also attach writing to their business stands. 4) Determining the location or place of business where traders choose a business location that has a high level of crowd.